The Politicization of Parenthood
XII, 312 p.
Keywords: Currently, families are being subjected to increasing public attention with interest focusing on their potential strengths and weaknesses in determining how well children do at school. Parents and children are at the forefront of the welfare state and socio-educational activities in current programs and policies. This book examines the resulting changes in the relationship between families and the state, and the shifting borders of public and private responsibility in education, child care, and childrearing. It considers international and national debates that underline the fact that issues in private life are increasingly entering the public discourse and becoming subject to attempts at socio-political control. Finally, it discusses the growing politicization of parenthood in the (post) welfare state and the increasing attention being paid to the structural conditions of gainful employment and child care as well as to the current relations between the genders.